The busy periphery urban systems of the Balkan and Danube provinces (2nd - 3rd c. AD) - Donev, Damjan, 1979- (Archaeopress archaeology., 2019)
This book reconstructs the urban geography of the Balkan and Danube provinces during the Severan dynasty, mapping the variable developments of the urban network between and within the sub-regions of that part of the Roman Empire. It examines the role of the town in Roman provincial society, and the prerequisites for their emergence and prosperity.